Behind and beyond the standard(ization) trap: diversifying power sources by differentiating centralization and standardization - Lee, Junesoo (International Review of Public Administration, 2024)
Standardization, often seen as a means to increase power through uniform working methods, has both benefits and drawbacks. Scholars and practitioners highlight the risk of a ‘standard(ization) trap’, where initial benefits lead to unforeseen costs. This study reviews literature and practices in standardization, identifying confusion between two power sources: substance power, concerning WHETHER to standardize, and decision-making power, dealing with WHO standardizes. It introduces a matrix differentiating these sources, offering insights into standardization methods. This matrix proposes four archetypes of standardization: centralized standardization, centralized de-standardization, decentralized standardization, and decentralized de-standardization. These archetypes offer theoretical and practical insights for addressing standardization challenges.